Hubungan Antara Tingkat Pengetahuan Tentang Anemia Dengan Kejadian Anemia Pada Santriwati Di Pondok Pesantren Darul Amin Kecamatan Waru Kabupaten Pamekasan - Irma Taufani (Akademi Kebidanan Aifa Husada Madura, 2019)
White teenagers are more susceptible to anemia compared to young men, this is because teenage iron needs are three times greater than young men. Teenage girls every month experience menstruation which will automatically bleed. The purpose of this study was to find out the relationship between the level of knowledge about anemia with the incidence of anemia in female students at PP Darul Amin, Waru Pamekasan. The method of this research is descriptive analytic using a cross sectional approach. Sampling uses a simple formula formula of 97 resondents. Data analysis using the Sperman test rho. The results showed that there was a correlation between the level of knowledge about anemia and the incidence of anemia in santri in PP Darul Amin, Waru Pamekasan